Distributed Channel-Aware Quantization Based on Maximum Mutual Information - Sahar Movaghati; Masoud Ardakani (International Journal of Distributed Sensor Networks)
In distributed sensing systems with constrained communication capabilities, sensors' noisy measurements must be quantized locally before transmitting to the fusion centre. When the same parameter is observed by a number of sensors, the local quantization rules must be jointly designed to optimize a global objective function. In this work we jointly design the local quantizers by maximizing the mutual information as the optimization criterion, so that the quantized measurements carry the most information about the unknown parameter. A low-complexity iterative approach is suggested for finding the local quantization rules. Using the mutual information as the design criterion, we can easily integrate the effect of communication channels in the design and consequently design channel-aware quantization rules. We observe that the optimal design depends on both the measurement and channel noises. Moreover, our algorithm can be used to design quantizers that can be deployed in different applications. We demonstrate the success of our technique through simulating estimation and detection applications, where our method achieves estimation and detection errors as low as when designing for those special purposes.